Market Segmentation and Information Values of Earnings Announcements: Some Empirical Evidence from an Event Study on the Chinese Stock Market - GAO, Yu (Institutional Knowledge at Singapore Management University, 2002)
This paper investigates the trading activities of two distinct classes of shareholders, namely, the Chinese domestic investors and the foreign investors in the segmented Chinese A-share and B-share markets, respectively. We conduct an event study on the annual earnings announcements based on two different accounting standards: IAS and PRC GAAP. The earnings announcements based on IAS and PRC GAAP are value relevant. The investors in the B-share market react to both the IAS and PRC GAAP earnings announcements, while the investors in the A-share market pay more attention to the PRC GAAP earnings reports. In the B-share market, positive abnormal returns are associated with positive earnings surprise and negative abnormal returns go with negative earnings surprise. We find pre-event abnormal trading volumes without significant price changes for the A shares, which may be due to existing information in the A-share market prior to earnings announcements. The post-event abnormal trading volumes last for a longer period in the Ashare market than in the B-share market.